Observer-based anti-windup compensator design for nonlinear systems. Issue 18 (December 2019) - Saqib, Najam us; Rehan, Muhammad; Hussain, Muntazir; Zheng, Zewei
Abstract: This paper presents a method for observer-based nonlinear anti-windup compensator (AWC) design using decoupled architecture for the class of nonlinear systems under input saturation by considering the unavailability of state variables. Novel observer-based nonlinear decoupled and equivalent decoupled anti-windup compensator architectures are proposed for the class of nonlinear systems with input saturation and unmeasured states. The designed constraints are formulated by utilizing Lyapunov function, L 2 gain reduction, global sector condition and Lipschitz inequality. Linear matrix inequality (LMI) based conditions are derived for simultaneous design of dynamic nonlinear anti-windup compensator and the state observer gain. Global design of dynamic nonlinear anti-windup compensator and observer gain is provided in order to ensure global exponential L 2 stability of the closed-loop system. Furthermore, anti-windup compensation constraints using local exponential L 2 stability are also provided to ensure regional closed-loop stability and performance. In contrast to the conventional dynamic AWC schemes for nonlinear systems, the proposed approach can be employed when states of a system are not measurable. Numerical example of the nonlinear DC motor under input saturation is considered to demonstrate effectively of the proposed technique.